Optimization of used engine oil Furnace Design with Initial Heater - Sahbudin, Muhammad; Hermawan, Wawan; Sutejo, Agus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Used engine oil is a waste from various types of machinery that has potential as an alternative fuel. The viscous characteristics of used engine oil require viscosity adjustment to be utilized as fuel. Nowadays used engine oil burners are generally using an external heater as an initial preheater, which causes the thermal efficiency decreased. The aims of this study are optimizing the design of the used engine oil burner by adding an initial heater and to find the optimum operating conditions of the burner to improve thermal. The initial heater is a spiral-shaped heat exchanger around the flame inside the burner, using its heat to decrease the viscous of used engine oil, so the used engine oil can be used as burner fuel. This study is varying the combustion air flowrate at 3.2×10-3 kg/s, 4.6×10-3 kg/s, and 6.4×10-3 kg/s and fuel rates of 2.1×10-4 kg/s, 3.1×10-4 kg/s, and 4.3×10-4 kg/s so the best performance of the burner will be observed. The results were obtained the best burner performance air flowrate of 4.6×10-3 kg/s and fuel flow rate of 4.3×10-4 kg/s, producing flue gas heat of 544°C, useful energy of 2.69 kW, and a resulting thermal efficiency of 59.54%. Keywords: Burner, Design optimization, Initial heater, Used engine oil, Viscosity.